Delays in third-line antiretroviral therapy and outcomes in North West province - Babalwa Majova; Ebrahim Variava; Neil Martinson (AOSIS, 2022)
Background: Rapid switching from second-line to third-line antiretroviral therapy (TLART) is crucial for achieving viral suppression and reducing illness related to ART failure. Objectives: This retrospective cohort study quantified the waiting periods for TLART initiation after virological failure on second-line therapy was detected, assessed factors associated with delays and assessed the outcomes of patients started on TLART. Method: Data were abstracted from records of individuals eligible for TLART, and the time to TLART initiation was calculated. Reasons for delays were categorised according to patient, clinician and administrative processes. Results: Fifty-four patients were eligible for TLART. The median delay from the date of first viral load 1000 copies/mL on second-line therapy to the start of TLART was 640 days (interquartile range [IQR]: 451-983 days). Of the patients that failed second-line and had an application for TLART, 41 (75.6%) were eventually initiated on TLART, and 11 (20.4%) died while waiting. Delays were primarily due to non-response to the first unsuppressed viral load while on second-line ART: 467 days (IQR: 232-803 days). Conclusion: This study showed a prolonged waiting period for TLART initiation mainly between detected high viral load to requesting of resistance tests; many factors could have contributed, including clinicians' delayed responses to elevated viral loads. Mortality was high before TLART could be initiated. The process of TLART initiation needs to be made more efficient. Healthcare services should be strengthened to (1) recognise and manage virological failure early and identify those eligible for resistance testing, (2) ensure access to resistance testing and appropriately skilled clinicians, and (3) streamline approvals and delivery of TLART.